2005
DOI: 10.1016/j.jcrs.2005.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pupil and optical zone diameter on higher-order aberrations after wavefront-guided myopic LASIK

Abstract: The OZ zone to pupil ratio (fractional clearance) had a significant impact on HOA induction after wavefront-guided LASIK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 41 publications
3
25
0
3
Order By: Relevance
“…With both PDs, smaller OZ diameters were correlated with higher induction of coma RMS and Z 4 0 . Studies show that the higher the relation between the OZ and PD, 26,27 the smaller the induction of spherical aberrations after LASIK. [27][28][29] The present study confirmed the importance of fractional clearance (FC, the OZ to PD ratio) 27 : The OZ diameter plays a marginal role if FC is high (in this study, 3.5 mm pupil); if FC is lower (in this study, 6.0 mm), it was significantly inversely correlated with HOA induction (Figure 2, A and B).…”
Section: Programmed Optical Zone Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…With both PDs, smaller OZ diameters were correlated with higher induction of coma RMS and Z 4 0 . Studies show that the higher the relation between the OZ and PD, 26,27 the smaller the induction of spherical aberrations after LASIK. [27][28][29] The present study confirmed the importance of fractional clearance (FC, the OZ to PD ratio) 27 : The OZ diameter plays a marginal role if FC is high (in this study, 3.5 mm pupil); if FC is lower (in this study, 6.0 mm), it was significantly inversely correlated with HOA induction (Figure 2, A and B).…”
Section: Programmed Optical Zone Diametermentioning
confidence: 99%
“…Studies show that the higher the relation between the OZ and PD, 26,27 the smaller the induction of spherical aberrations after LASIK. [27][28][29] The present study confirmed the importance of fractional clearance (FC, the OZ to PD ratio) 27 : The OZ diameter plays a marginal role if FC is high (in this study, 3.5 mm pupil); if FC is lower (in this study, 6.0 mm), it was significantly inversely correlated with HOA induction (Figure 2, A and B). The influence of OZ diameter on coma induction could only be determined by looking at coma RMS values that became larger with higher positive or negative shifts of the individual coma terms and therefore were more sensitive to random decentration of the OZ than individual coma terms.…”
Section: Programmed Optical Zone Diametermentioning
confidence: 99%
“…Refractive surgery with a relatively small OZ can produce higher-order aberrations (HOAs), poor optical quality, reduced contrast sensitivity, and increased glare disability. [2][3][4][5][6] Despite the use of large ablation zones, issues related to quality of vision have been described in many clinical studies of photorefractive keratectomy and laser in situ keratomileusis. 3,4,[7][8][9] The most common patient complaints are glare, halos, and diminished night vision.…”
mentioning
confidence: 99%
“…It is well-known that pupil size had a significant influence on the residual wavefront aberration RMS, especially for the condition of optical zone diameter larger than pupil size [21]. Also, our previous results indicated that the change in HOA root mean square and spherical aberration was significantly correlated with the optical zone to pupil ratio [7].…”
Section: Discussionmentioning
confidence: 80%